Seasonality of the Microbial Community Composition in the North Atlantic - Bolaños, Luis M.; Choi, Chang Jae; Worden, Alexandra Z.; Baetge, Nicholas; Carlson, Craig A.; Giovannoni, Stephen (Frontiers in Marine Science, 2021)
Planktonic communities constitute the basis of life in marine environments and have profound impacts in geochemical cycles. In the North Atlantic, seasonality drives annual transitions in the ecology of the water column. Phytoplankton bloom annually in spring as a result of these transitions, creating one of the major biological pulses in productivity on earth. The timing and geographical distribution of the spring bloom as well as the resulting biomass accumulation have largely been studied using the global capacity of satellite imaging. However, fine-scale variability in the taxonomic composition, spatial distribution, seasonal shifts, and ecological interactions with heterotrophic bacterioplankton has remained largely uncharacterized. The North Atlantic Aerosols and Marine Ecosystems Study (NAAMES) conducted four meridional transects to characterize plankton ecosystems in the context of the annual bloom cycle. Using 16S rRNA gene-based community profiles we analyzed the temporal and spatial variation in plankton communities. Seasonality in phytoplankton and bacterioplankton composition was apparent throughout the water column, with changes dependent on the hydrographic origin. From winter to spring in the subtropic and subpolar subregions, phytoplankton shifted from the predominance of cyanobacteria and picoeukaryotic green algae to diverse photosynthetic eukaryotes. By autumn, the subtropics were dominated by cyanobacteria, while a diverse array of eukaryotes dominated the subpolar subregions. Bacterioplankton were also strongly influenced by geographical subregions. SAR11, the most abundant bacteria in the surface ocean, displayed higher richness in the subtropics than the subpolar subregions. SAR11 subclades were differentially distributed between the two subregions. Subclades Ia.1 and Ia.3 co-occurred in the subpolar subregion, while Ia.1 dominated the subtropics. In the subtropical subregion during the winter, the relative abundance of SAR11 subclades “II” and 1c.1 were elevated in the upper mesopelagic. In the winter, SAR202 subclades generally prevalent in the bathypelagic were also dominant members in the upper mesopelagic zones. Co-varying network analysis confirmed the large-scale geographical organization of the plankton communities and provided insights into the vertical distribution of bacterioplankton. This study represents the most comprehensive survey of microbial profiles in the western North Atlantic to date, revealing stark seasonal differences in composition and richness delimited by the biogeographical distribution of the planktonic communities.